Improving The Quality Of Higher Education In The Era Of Independent Learning At Swadarma Institute Of Technology And Business - Sucahyo, Nur; Wibowo, Agung Hardianto; Sauri, R. Supyan (UNIVERSITAS PAKUAN, 2024)
Higher education shapes skilled workers and advances society and the economy. Higher education must adapt to digital transformation and globalization. Merdeka Belajar directs the development of higher education by granting students increased autonomy. Descriptive qualitative methodology is employed in this study to elucidate and depict endeavors aimed at enhancing the caliber of higher education, with a specific focus on the assistance provided to the Merdeka Belajar program at the Swadarma Institute of Technology and Business. Through the utilization of document analysis, interviews, and observations, this research emphasizes the critical significance of student autonomy in the process of devising their own educational experiences. Enhancing the caliber of education and guaranteeing that graduates are adequately equipped to navigate the ever-changing labor market are integral components of a prosperous Merdeka Belajar policy. This study establishes a fundamental basis for other tertiary institutions to emulate by emphasizing the following: lecturer empowerment, student autonomy, innovation, curriculum adaptability, cultivation of soft skills, ongoing assessment, and effective utilization of technology. The research implications encompass recommendations for the advancement of higher education during the Merdeka Belajar era and contributions to the internal development of institutions.